Development of a knowledge-based feedback assistance system of product use information for product improvement. (1st January 2014) - Dienst, Susanne; Fathi, Madjid; Abramovici, Michael; Lindner, Andreas
Due to technological advancement, an increase in creating and storing digital data can be observed today, for instance throughout the product life cycle. Through especially product use, a large number of data are created. The data are mainly used during the product use phase (e.g. condition-based maintenance). However, those data can be used as feedback to generate knowledge and support the product developer through improving future product generations. This paper presents development and prototypical realisation of a feedback assistance system for the management, analysis and visualisation of feedback data. The system supports a product developer by improving the process of decision-making to discover development potentials. Thereupon, four modules have been developed to analyse related indicators statistically and to diagnose machine failures. The obtained knowledge about the current condition of machines should then be deployed to improve the next machine generations utilising the modules for decision support and prediction.